Programmable Gene Knockdown in Diverse Bacteria Using Mobile‐CRISPRi. Issue 1 (17th December 2020) - Banta, Amy B.; Ward, Ryan D.; Tran, Jennifer S.; Bacon, Emily E.; Peters, Jason M.
Abstract: Facile bacterial genome sequencing has unlocked a veritable treasure trove of novel genes awaiting functional exploration. To make the most of this opportunity requires powerful genetic tools that can target all genes in diverse bacteria. CRISPR interference (CRISPRi) is a programmable gene‐knockdown tool that uses an RNA‐protein complex comprised of a single guide RNA (sgRNA) and a catalytically inactive Cas9 nuclease (dCas9) to sterically block transcription of target genes. We previously developed a suite of modular CRISPRi systems that transfer by conjugation and integrate into the genomes of diverse bacteria, which we call Mobile‐CRISPRi. Here, we provide detailed protocols for the modification and transfer of Mobile‐CRISPRi vectors for the purpose of knocking down target genes in bacteria of interest. We further discuss strategies for optimizing Mobile‐CRISPRi knockdown, transfer, and integration. We cover the following basic protocols: sgRNA design, cloning new sgRNA spacers into Mobile‐CRISPRi vectors, Tn 7 transfer of Mobile‐CRISPRi to Gram‐negative bacteria, and ICE Bs1 transfer of Mobile‐CRISPRi to Bacillales. © 2020 The Authors. Basic Protocol 1 : sgRNA design Basic Protocol 2 : Cloning of new sgRNA spacers into Mobile‐CRISPRi vectors Basic Protocol 3 : Tn 7 transfer of Mobile‐CRISPRi to Gram‐negative bacteria Basic Protocol 4 : ICE Bs1 transfer of Mobile‐CRISPRi to Bacillales Support Protocol 1 : Quantification of CRISPRi repression using fluorescent reporters Support Protocol 2 : Testing for gene essentiality using CRISPRi spot assays on plates Support Protocol 3 : Transformation of E. coli by electroporation Support Protocol 4 : Transformation of CaCl2 ‐competent E. coli